1995
DOI: 10.1136/jcp.48.5.463
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid antoantibodies and the response to thyrotropin releasing hormone in patients with subclinical hypothyroidism.

Abstract: Aim-To evaluate the clinical usefulness of the thyrotropin releasing hormone (TRH) test and estimation of thyroid autoantibody concentrations in patients with borderline raised thyroid stimulating hormone (TSH). Methods-The records of 34 consecutive patients with persistent borderline increased TSH (4.4-9.9 mU/l) referred to the Medical Investigation Unit were reviewed. MethodsThe records of 34 (30 women and four men) consecutive patients referred over an 18 month period were reviewed. The patients were aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2001
2001
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Finally, others have suggested that a ΔTSH cutoff of 25 to 30 mU/L or a 6-fold rise in TSH at 20 minutes are the cutoffs that suggest hypothyroidism. 4,11 We used a more intuitive method to arrive at our estimated cutoff of 20 mU/L and suggest this as more optimal. We do not advocate the fold-response as it varies with the basal TSH.…”
mentioning
confidence: 99%
“…Finally, others have suggested that a ΔTSH cutoff of 25 to 30 mU/L or a 6-fold rise in TSH at 20 minutes are the cutoffs that suggest hypothyroidism. 4,11 We used a more intuitive method to arrive at our estimated cutoff of 20 mU/L and suggest this as more optimal. We do not advocate the fold-response as it varies with the basal TSH.…”
mentioning
confidence: 99%